Financial Impact on Aviation Industry Before and During Covid-19: Passenger Demand as Moderator - Farra Nurdeanna Binti Saiful Nizam; Maryam Jameelah Mohd Hashim; Nur Zahidah Bahrudin; Nur Afizah Mohamad Arifin; Mohamad Harizayani Md Yahya (Information Management and Business Review, 2024)
This study analyses the impact of the pandemic on the financial performance of airlines, with a specific focus on financial ratios. The travel limitations imposed as a result of the pandemic, coupled with a significant decline in passenger demand, resulted in significant financial losses. This study investigates how passenger demand moderates the relationship between financial ratios and the performance of the aviation industry. This study gathered data from 20 premier Asian airline companies, as acknowledged by Skytrax. The data was collected from 2016 to 2022, with the timeframe from 2016 to 2019 designated as the 'pre-Covid19' period, and the timeframe from 2020 to 2022 designated as the 'during Covid19' period. The study uses static panel data analysis to accomplish its objective by integrating cross-sectional and time series analysis. Based on this analysis, it was determined that the company's financial condition had a substantial impact on its performance and operating worth before the COVID-19 outbreak. This influence was observed across all variables, except TATO (Total Assets Turnover). However, the company’s financial condition does not affect its performance during the COVID-19 outbreak. This is due to the implementation of government initiatives and bailouts offered some respite, while also underscoring pre-existing structural weaknesses within the business. The results emphasize the crucial requirement for airlines to implement adaptable financial strategies and strong risk management techniques to successfully navigate future disruptions. Hence, the aviation sector should embrace a comprehensive strategy centered on minimizing expenses, expanding income sources, and implementing digitalization.